Using technology in teaching Arabic calligraphy skills - Alowaydhi, Wafaa Hafize; Bagies, Afrah Salem (Journal of Educational and Psychological Sciences, 2020)
The study dealt with the issue of teaching Arabic calligraphy skills using technology with the aim of making a decision towards including them in the Arabic language courses, and to achieve the goal of the study, the two researchers used the descriptive survey method and an electronic questionnaire was designed to refer to the study population consisting of all teachers, teachers, supervisors and Arabic language supervisors who specialize in teaching them in the universities of the Kingdom of Saudi Arabia. Participants in the referendum (400) individuals, then the opinions were treated statistically using percentages, and the percentage of supporters and opponents limited its teaching and the reasons for each team. The result appeared in favor of the opponents by 85.4%, and among the most important reasons for the opposition is that the teaching of calligraphy is a basic written skill that must be studied and practiced in a real, tangible, real way that must be taught by hand and the student’s training in it in order to acquire the skill and develop away from technology, and the percentage of supporters was 14.6% and one of the most important reasons for their support The student’s use of the computer is a modern skill that the student needs a lot. So I think the time has come to take advantage of the long training time on the skills of beauty and speed in training the student to use the keyboard quickly, and teach him from the location of choosing fonts, and perhaps it will evolve to his teaching using Arabic script in the letter And other skills.
Keywords: technology; skills; calligraphy